Diagnostic and therapeutic approach to drug-resistant juvenile myoclonic epilepsy. (2nd November 2021) - Ascoli, Michele; Mastroianni, Giovanni; Gasparini, Sara; Striano, Pasquale; Cianci, Vittoria; Neri, Sabrina; Bova, Valentina; Mammì, Anna; Gambardella, Antonio; Labate, Angelo; Aguglia, Umberto; Ferlazzo, Edoardo
ABSTRACT: Introduction: Juvenile myoclonic epilepsy (JME), also known as Janz syndrome, is a common form of generalized epilepsy of presumed genetic origin representing up to 10% of all epilepsy cases. Despite adequate anti-seizure medication (ASM) treatment, seizures persist in one-third of JME patients. Areas covered: A literature search was conducted using Pubmed search on the topics of drug-resistant JME. Expert Opinion: About 30% of JME patients are drug-resistant. Valproate (VPA) is considered the first-choice drug. In women of childbearing potential, levetiracetam (LEV) should represent the first-choice treatment. Alternative monotherapy or add-on therapy should be considered in subjects with resistant seizures after the exclusion of pseudo-drug resistance. The choice of the add-on ASM depends on the predominant seizure type. In subjects with persistent bilateral tonic-clonic seizures, LEV or lamotrigine should be firstly considered. In patients with difficult-to-treat myoclonic seizures, clonazepam or LEV are recommended. In case of persistent absences, ethosuximide should be considered. With appropriate selection and safeguards in place, VPA should remain available as an option in women of childbearing potential whose seizures are resistant to other treatments.